The mammalian type II gonadotropin-releasing hormone receptor : cloning, distribution and role in gonadotropin gene expression - Van Biljon, Wilma (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2006.